Indirect versus direct detection methods of Trichinella spp. infection in wild boar (Sus scrofa) - Maria Angeles Gómez-Morales; Alessandra Ludovisi; Marco Amati; Ennio Bandino; Gioia Capelli; Franco Corrias; Luca Gelmini; Alberigo Nardi; Cristina Sacchi; Simona Cherchi; Marco Lalle; Edoardo Pozio (Parasites & Vectors, 2014)
Abstract Background Trichinella spp. infections in wild boar (Sus scrofa), one of the main sources of human trichinellosis, continue to represent a public health problem. The detection of Trichinella spp. larvae in muscles of wild boar by digestion can prevent the occurrence of clinical trichinellosis in humans. However, the analytical sensitivity of digestion in the detection process is dependent on the quantity of tested muscle. Consequently, large quantities of muscle have to be digested to warrant surveillance programs, or more sensitive tests need to be employed. The use of indirect detection methods, such as the ELISA to detect Trichinella spp. infections in wild boar has limitations due to its low specificity. The aim of the study was to implement serological detection of anti-Trichinella spp. antibodies in meat juices from hunted wild boar for the surveillance of Trichinella spp. infections. Methods Two tests were used, ELISA for the initial screening test, and a specific and sensitive Western blot (Wb) as a confirmatory test. The circulation of anti-Trichinella IgG was determined in hunted wild boar muscle juice samples in 9 provinces of 5 Italian regions. Results From 1,462 muscle fluid samples, 315 (21.5%, 95% C.I. 19.51-23.73) were tested positive by ELISA. The 315 ELISA-positive muscle fluid samples were further tested by Wb and 32 (10.1%, 95% C.I. 7.29-13.99) of these were positive with a final seroprevalence of 2.2% (95% C.I 1.55-3.07; 32/1,462). Trichinella britovi larvae were detected by artificial digestion in muscle tissues of one (0.07%, 95%C.I. 0.01-0.39) out of the 1,462 hunted wild boars. No Trichinella spp. larvae were detected in Wb-negative wild boar. From 2006 to 2012, a prevalence of 0.017% was detected by muscle digestion in wild boar hunted in the whole Italian territory. Conclusions The combined use of both serological methods had a sensitivity 31.4 times higher than that of the digestion (32/1,462 versus 1/1,462), suggesting their potential use for the surveillance of the Trichinella spp. infection in wild boar populations.